Kemampuan Pemecahan Masalah Matematis Kelompok Matematika Ilmu Alam dan Ilmu-Ilmu Sosial - Holidun, Holidun; Masykur, Rubhan; Suherman, Suherman; Putra, Fredi Ganda (Desimal: Jurnal Matematika, 2018)
The purpose of this study is to find out how the analysis of the mathematical problem-solving ability of students in Mathematics of Natural Sciences (MIA) and Social Sciences (IIS) groups in terms of interest in learning the mathematics of learners. This research is a qualitative research type analysis. The data collected in this research is done by a triangulation technique which is done when the researcher analyzes the problem-solving ability of mathematical learners. The technique of data validity used in this research is triangulation technique. Data analysis techniques used are Model Miles and Huberman, IE data reduction, data presentation, and conclusion. The results of the discussion show students with high-interest categories can solve the problem of each of the stages of problem-solving correctly. Students with moderate interest categories in solving the given problem, able to solve problem problems and meet all the indicators, but in some other stages are still less systematic in the settlement. Students with low-interest categories are only able to finish in the stages of understanding the problem and planning the problem, although not maximal yet, and have not been able to finish the other stages.